KORELASI LINGKUNGAN KELUARGA DENGAN HASIL BELAJAR ILMU PENGETAHUAN SOSIAL SISWA KELAS VI SEKOLAH DASAR NEGERI 15 PONTIANAK SELATAN - Rima Andriyani; Siti Halidjah; Rio Pranata (Universitas Tanjungpura, 2022)
This study aims to obtain an objective picture of the correlation between family environment and social science learning outcomes for sixth graders at the State Elementary School 15, South Pontianak. The method used in this study is a descriptive method with a form of correlation study research. The sample in this study were 11 students and 12 students of class VI, totaling 23 people. Samples were taken using nonprobability sampling technique with saturated sampling type. Data collection techniques and tools used are indirect communication with data collection tools in the form of questionnaires and documentary study techniques, namely data collection tools in the form of even semester report cards in Social Science subjects. The results showed that the family environment was classified as good, namely 85.87% and student learning outcomes in Social Science lessons obtained an average of 85.22 which was classified as good because it was in the range of 83-90. There is a strong relationship between the family environment and student learning outcomes. This value is then compared with rtable at a significant level of 5% for N=23 which is 0.413. Thus rcount > from rtable or 0.782 > 0.413. In this study, the alternative hypothesis (Ha) is accepted and the null hypothesis (Ho) is rejected because the value of rcount is greater than rtable, which means that there is a correlation or relationship between the family environment and the learning outcomes of Social Science students of class VI Elementary School 15 South Pontianak.